New record of the species Pseudorinelepis genibarbis (Loricariidae: Rhinelepinae) for the Caquetá river basin, Colombia - Celis-Granada, Monica Silrey; Medina, Sebastián; Beltrán, Camilo (Zootaxa, 2019)
The Neotropical fish family Loricariidae is the most diverse family of catfishes (order Siluriformes) and the fifth largest fish family, with approximately 993 valid species. The species of the family are geographically distributed from Costa Rica in Central America to Argentina in South America and are grouped into 83 genera and the following six subfamilies: Hypoptopomatinae, Hypostominae, Loricariinae Delturinae, Lithogeninae and Rhinelepinae (Roberto et al., 2006, Birindelli et al., 2007, Corea et al., 2014, Eschmeyer & Fong, 2019).